Produksi pestisida nabati dari serai, cengkeh, dan lada di Desa Sanggrahan, Kabupaten Nganjuk - Rasyadan Taufiq Probojati; Nina Lisanty; Achmad Masykur Ghazali (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2022)
Lemon grass and cloves contain essential oils that are against pest. Thus, they have the potential to be used as main ingredients in the manufacture of botanical pesticides. The teamwork program of the Faculty of Agriculture, Kadiri University formulated both ingredients to produce biopesticide suitable for common pests on shallot plant. It was hoped that the information and knowledge can be spread to the community, particularly shallot farmers, to be able to process natural ingredients for botanical pesticides. The farmers are always constrained by armyworm attacks on their plants. Community service was carried out to educate and socialize the production of the biopesticide at residents' homes in Sanggrahan Village, Gondang District, Nganjuk Regency, East Java Province. The main target of this program was the shallot farming community in the area. Several implementation stages included lectures, training on making pesticides, producing biopesticides, making leaflets, evaluating, and assisting the results of application of biopesticides. The community service activity was carried out smoothly and the community was enthusiast to take part in the activitySerai dan cengkeh memiliki kandungan minyak atsiri yang bersifat beracun, sehinga berpotensi sebagai bioaktivitas terhadap serangan hama. Disisi lain, serai dan cengkeh memiliki potensi yang dapat dijadikan sebagai bahan alam dalam pembuatan pestisida nabati. Melalui program kerja tim pengabdian fakultas pertanian Universitas Kadiri, diharapkan masyarakat mampu mengolah bahan alami untuk pestisida nabati. Program ini diharapkan dapat membantu mengatasi para petani bawang merah yang setiap musim tanam selalu terkendala dengan serangan hama ulat grayak. Pengabdian masyarakat dilaksanakan di rumah warga di Desa Sanggrahan, Kecamatan Gondang, Kabupaten Nganjuk, Provinsi Jawa Timur. Sementara itu, sasaran pengabdian ini adalah masyarakat petani bawang merah di Desa Sanggrahan. Beberapa tahapan pelaksanaan diataranya adalah ceramah, pelatihan pembuatan pestisida, memproduksi pestisida nabati, membuat leaflet, dan pendampingan dalam implementasi hasil pembuatan pestisida nabati. Hasil kegiatan pengabdian kepada masyarakat ini dilaksanakan dengan lancar dan respon masyarakat sangat antusias untuk mengikuti kegiatan ini.